Comparative lipid profile study between ischemic and haemorrhagic stroke - Singh, Vijaiendre; Bajia, Kamalesh Kumar; Ram, Chaina; Kumar, Ajay; Mathur, Ajay; Bansal, Pradeep Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Stroke is one of the major global health problems. Stroke is the most common clinical manifestation of cerebrovascular disease of which more than 99% are due to arterial involvement and less than 1% due to venous involvement in the form of Cerebral Venous Thrombosis (CVT). Among arterial causes 85% are due to infarction and 15% due to haemorrhage.1,2 There is difference in serum lipid levels in subtypes of strokes to guide lipid-lowering therapy which can reduce incidence of stroke and stroke related mortality by adapting primary and secondary preventive measures.3,4 Authors have endeavoured to correlate severity of lipid derangement and stroke. Methods: In this study 64 consecutive eligible ischaemic stroke cases and 64 eligible hemorrhagic stroke cases would be included. Cases of strokes will be divided into ischaemic and hemorrhagic as per clinical features and with help of brain imaging by CT scan and MRI at the time of admission and 8 hour fasting lipid profile was collected from all cases. All this information will be filled in preformed format. Results: Serum lipid profile of two categories of stroke showed raised serum total cholesterol in 39.1% patients of ischaemic stroke in contrast to 18.8% patients with haemorrhagic stroke (p=0.019). Stroke patients showed raised in LDL cholesterol in 29.7% patients of ischaemic stroke in contrast to 9.4% patients with haemorrhagic stroke, (p=0.007). Conclusions: Based on the finding of our study we conclude that ischemic stroke patient had higher lipid derangement as compare to haemorrhagic stroke in terms of raise total cholesterol, LDL cholesterol and decrease HDL cholesterol.